1994
DOI: 10.1111/j.1151-2916.1994.tb05370.x
|View full text |Cite
|
Sign up to set email alerts
|

Dense Al2O3/ZrO2 Particulate Composites by Free Sintering of Coated Powders

Abstract: Composite powders, prepared by coating coarse ZrO, particles with fine A1,0, powder using a chemical precipitation technique, were compacted and sintered freely at a constant heating rate of 4"C/min to -1600°C. Composites containing up to -30 vol% inclusions were sintered to nearly full density under the same conditions used for the unreinforced matrix. Furthermore, the sintering kinetics were not influenced significantly by the inclusion volume fraction. The sinterability of the composites formed from the coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…In multi‐component material systems such as ceramic matrix composites (CMCs), in addition to all the aforementioned materials and processing effects, the effects of secondary phases (e.g., rigid inclusions) on sintering and anisotropic shrinkage must also be considered. Although several sintering studies have been performed on multi‐phase material systems, most of them have focused on processing–microstructure development relationships 20–24 . These studies revealed that the presence of non‐sinterable inclusions in a green body results in constrained sintering as well as sintering damage, such as crack‐like flaws, planar arrays of voids, or isolated pores 21,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In multi‐component material systems such as ceramic matrix composites (CMCs), in addition to all the aforementioned materials and processing effects, the effects of secondary phases (e.g., rigid inclusions) on sintering and anisotropic shrinkage must also be considered. Although several sintering studies have been performed on multi‐phase material systems, most of them have focused on processing–microstructure development relationships 20–24 . These studies revealed that the presence of non‐sinterable inclusions in a green body results in constrained sintering as well as sintering damage, such as crack‐like flaws, planar arrays of voids, or isolated pores 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that the presence of non‐sinterable inclusions in a green body results in constrained sintering as well as sintering damage, such as crack‐like flaws, planar arrays of voids, or isolated pores 21,22 . The effects of inclusions on sintering are more complicated in CMCs and may cause retardation in densification by the following mechanisms: (i) transient stresses due to differential sintering between the inclusions and the matrix, (ii) the formation of a rigid network between inclusions above a critical volume fraction, and (iii) the disruption of particle packing in the matrix near the inclusions 23,24 . Several models have been developed to predict the sintering behavior of powder compacts containing rigid inclusions with an emphasis on predicting the stresses generated by the inclusions on the matrix 25–29 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of precoated particles or whiskers was found to be very effective in ceramic/ceramic composites for both the dispersion of the reinforcement phase and the pressureless sintering to nearly full densities. [15][16][17] Generally, precoating reinforcement or matrix powders with a precursor of the matrix phase was shown to enhance densification and dispersion characteristics not only in composites but also in monolithic systems like SiC, Si 3 N 4 , and mullite. 18 -23 The aim of the present work was to facilitate the advantages of both processes (sol-gel processing using alumina seeds, as well as precoating of the SiC particles) to develop alumina/SiC nanocomposites with a uniform and fine microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Os pós ultrafinos contribuem positivamente no processo de sinterização, mas também podem gerar grandes dificuldades de processamento HU;RAHAMAN, 1994;STERNITZKE, 1997 tempo, o calor é gerado em toda a amostra e de dentro para fora, provocando a formação de gradientes de temperatura e fluxos de calor invertido (BORRELL et al, 2013;SUTTON,1996). Com isso, peças grandes são rápida e uniformemente aquecidas, evitando a geração de grandes tensões térmicas que, consequentemente, causariam trincas ou danos ao material (SCHIFFMAN, 1995).…”
Section: Processamento De Pós Ultrafinosunclassified